Optimizing Village Wealth Through the Transition to BUMDes in Indonesia - Moch Rifqi Tamaputra; Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2024)
This research examines the regulation of transitioning village assets to Village-Owned Enterprises (BUMDes) based on Village Law, highlighting shifts in dispute resolution methods. Using a normative method with statutory and historical approaches, the study identifies challenges in optimizing village head authority and effective supervision by regional heads. Key findings show the transition process involves initiation and agreements between BUMDes and village government, with tailored dispute resolution methods including mediation and litigation. Effective regulations and collaboration between officials and asset managers can enhance BUMDes' self-sufficiency, benefiting local economies and village welfare while ensuring transparency and community participation.Highlight: Transition Process: Village assets to BUMDes via initiation and agreements. Dispute Resolution: Methods include mediation, village discussions, and litigation. Regulatory Challenges: Enhance village head authority and regional supervision. Keywoard: Village assets, BUMDes, Village Law, Dispute resolution, Normative method